Optimum spacing between grooved tubes: an experimental study - Afzal, Asif; A. D., Mohammad Samee; R. K., Abdul Razzak; Khan, Sher Afghan; Khan, Hurmatulla (The Korean Society of Mechanical Engineers, 2020)
An experimental study on the optimum spacing between grooved tubes is reported in this paper. Two grooved tubes having a pitch of 10 mm and 15 mm and a plain tube were considered for the heat transfer analysis. The spacing between two tubes with the same pitch was varied from 10 mm to 35 mm with a step size of 5 mm. The velocity of air flowing over the tube surfaces was changed from 0.4 m/s to 1 m/s using a blower fan. Based on Nusselt number (Nu) the optimum spacing between the tubes was decided. The optimum spacing between grooved tubes of pitch 10 mm and 15 mm was compared with that of plain tubes. From the experimental analysis, it was noticed that with an increase in air velocity (increase in Reynolds number) the tube surface temperature reduced irrespective of any tube considered. Nu increased with an increase in air velocity for all the tubes. The important conclusion drawn from the present study was that there exists a limiting spacing (optimum) between the tubes above which no change in Nu was observed. The spacing of 30 mm was found to be the optimum spacing between the tubes irrespective of its surface geometry modifications.